2020
DOI: 10.1186/s12917-020-02333-3
|View full text |Cite
|
Sign up to set email alerts
|

Perilesional photobiomodulation therapy and physical rehabilitation in post-operative recovery of dogs surgically treated for thoracolumbar disk extrusion

Abstract: Background: Recent studies have reported contrasting results of the effects of laser therapy on post-operative intervertebral disk herniation, with a lack of evidence-based advantages of this modality within a rehabilitation protocol. The aim of this study was to report the clinical effects of photobiomodulation therapy within a post-operative rehabilitation protocol in dogs submitted to surgery for thoracolumbar disk extrusion. Twenty-four dogs were included in the study (12 dogs treated with laser therapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
1
13
0
2
Order By: Relevance
“…In dogs with incomplete injuries, rehabilitation also did not impact the rate of recovery of walking, walking coordination, proprioceptive placing or muscle mass 80 . One RCT excluded DPN dogs (80), and the other was not adequately powered to evaluate them; evidence is conflicting regarding the role for rehabilitation in these severely affected dogs 78,79,152,211‐216 . Study populations and rehabilitation protocols vary widely, and control groups frequently are lacking.…”
Section: Physical Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…In dogs with incomplete injuries, rehabilitation also did not impact the rate of recovery of walking, walking coordination, proprioceptive placing or muscle mass 80 . One RCT excluded DPN dogs (80), and the other was not adequately powered to evaluate them; evidence is conflicting regarding the role for rehabilitation in these severely affected dogs 78,79,152,211‐216 . Study populations and rehabilitation protocols vary widely, and control groups frequently are lacking.…”
Section: Physical Rehabilitationmentioning
confidence: 99%
“… There is conflicting evidence from 2 unblinded studies 116,152 Cadaveric study reported lower irradiance at the level of the spinal cord than has been proposed as necessary to modulate the area after SCI. …”
Section: Neuroprotective Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It has been described in the management of canine elbow osteoarthritis, chronic gingivostomatitis, wound healing, and postoperative period. [8][9][10][11] Despite the increasing number of reports on the potential uses of PBMT, there is still a need to outline specific protocols for the different conditions being treated. 10 Pain is a multidimensional experience, encompassing more than just a functional aspect.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Moreover, chronic wounds require intensive standard wound care; however, this is sometimes insufficient to promote healing. At present, photobiomodulation therapy (PBMT) can be used as adjunctive therapy for improving wound healing in veterinary medicine [3,4], dentistry [5], and medicine [6,7]. PBMT involves the use of therapeutic light, including laser, light-emitting diode, and broadband light, in the visible and infrared spectrum [8].…”
Section: Introductionmentioning
confidence: 99%